Background History, Clinical Presentation and Laboratory Profile in Cases of Suspected Neurometabolic Disorders - Mahbub, Mustafa; Azam, AZM Mosiul; Mazumder, Suraj C; Debnath, Bithi; Khan, Naila Zaman (Bangladesh Journal of Child Health, 2016)
Background : Neurometabolic disorders (NMD) in children may present at any age with a wide range of clinical manifestations. Unexplained or intractable seizure is one of the important associations. Consanguinity, regression of development and sibling death are the clues to suspect neurometabolic disorders when laboratory support is limited. Laboratory findings however, provide the confirmatory diagnosis which is unavailable in Bangladesh. Objectives : To determine the association of consanguinity, regression of development, seizures, EEG findings and other laboratory investigations in children suspected to have neurometabolic disorders and to aid clinicians working in resourcepoor countries. Methodology : A retrospective analysis was done from the records of the patients suspected to have neurometabolic disorders admitted in the department of Neurosciences, Dhaka Shishu Hospital, Dhaka during the period of July 2007 to February 2011. Tandem Mass Spectrometry (TMS), biotinidase activity and other enzyme assay were done through a private laboratory in New Delhi, India. Results : Total 128 children were studied and the parents of 39 (31%) had history of consanguineous marriage. Seizure was associated with 96 (75%) children and abnormal EEG findings were recorded in 83 (65%). Plasma ammonia was done in 98 cases and found to be increased in 53 (54%) cases. Plasma lactate was done in 94 cases and found high in 40 (43%). TMS were done in 111 (85%) children and abnormality were found in 70 (63%) cases. Serum biotinidase activity was advised for 41 children as per TMS result and measured in 25 children of which deficient activity was found in 17(68%); borderline in 4 (16%) and normal activity in 4 (16%) cases. Conclusion: Background history and clinical presentation followed by stepwise laboratory investigation is necessary to identify neurometabolic disorders. Early and appropriate intervention can reduce neurodisability in many situations. Bangladesh J Child Health 2015; VOL 39 (1) :24-29